Fingerprint Authentication System using a low-priced Webcam - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (2008)
A number of biometric techniques have been proposed for personal identification in the past. Among the vision-based ones, we can point out fingerprint, face, palm, ear, iris and retina recognition. Voice recognition or signature verification are the most widely known among the non-vision based ones. Signature verification requires the use of electronic tablets or digitizers for on-line capturing and optical scanners for on-line adaptation. These interfaces have some negative aspect that they are large and convoluted to use, increasing the intricacy of the whole identification system. On the other hand, scanners and cameras are much smaller and easy to handle, and are becoming all over in the current computer atmosphere. Lots of vision-based biometric techniques have been projected in the past for personal identification. We present a novel one based on visual capturing of fingerprints using a Webcam. However, there is an open issue to use webcam in stead of any scanner because of the low price, available in the market and easy to adjust anywhere. In this paper, we describe our implementation of the fingerprint authentication system using webcam having Pentium IV CPU, 256 RAM and a piece of transparent glass and a light source. Also, we describe a preprocessing technique based on gamma manipulation and gamma correction that can be executed to adjust lightness and intensities of the fingerprint image before fingerprint image enhancement and feature extraction.